Mitochondrial Dynamics and Mitophagy in the 6-Hydroxydopamine Preclinical Model of Parkinson's Disease - Maria F. Galindo; Maria E. Solesio; Sandra Atienzar-Aroca; Maria J. Zamora; Joaquín Jordán Bueso (Parkinson's Disease, 2012)
We discuss the participation of mitochondrial dynamics and autophagy in the 6-hydroxidopamine-induced Parkinson’s disease model. The regulation of dynamic mitochondrial processes such as fusion, fission, and mitophagy has been shown to be an important mechanism controlling cellular fate. An imbalance in mitochondrial dynamics may contribute to both familial and sporadic neurodegenerative diseases including Parkinson’s disease. With special attention we address the role of second messengers as the role of reactive oxygen species and the mitochondria as the headquarters of cell death. The role of molecular signaling pathways, for instance, the participation of Dynamin-related protein 1(Drp1), will also be addressed. Furthermore evidence demonstrates the therapeutic potential of small-molecule inhibitors of mitochondrial division in Parkinson’s disease. For instance, pharmacological inhibition of Drp1, through treatment with the mitochondrial division inhibitor-1, results in the abrogation of mitochondrial fission and in a decrease of the number of autophagic cells. Deciphering the signaling cascades that underlie mitophagy triggered by 6-OHDA, as well as the mechanisms that determine the selectivity of this response, will help to better understand this process and may have impact on human treatment strategies of Parkinson’s disease.